Odoo Software for Human Capital Training to Optimize Enterprise Resource Planning Efficacy for Students - Dian Juliarti Bantam (Psympathic : Jurnal Ilmiah Psikologi, 2022)
This research aimed to evaluate efficacy of Odoo Human Capital Training (OHCT) using the Classroom Action Research (CAR) method to optimize Enterprise Resource Planning Efficacy (ERPE) in a minimal contact environment. A purposive sampling technique was used to select forty participants from Psychology and Management study program, and divided into experimental and control groups. The nonequivalent control group design was employed with pretest and posttest, and the experimental group was subjected to a rigorous training program of 4-5 hours of training per day. Meanwhile, ERP-Efficacy Questionnaire (ERP-EQ) was used to measure ERPE, and data analysis was analyzed using the Non-Parametric Friedman Test. The results showed that OHCT can improve ERPE between pretest, posttest, and follow-up (χ2 (2, n = 20) = 27.195, p < .05), compared to the control group (χ2 (2, n = 20) = 4.081, p > .05). Based on these findings, it can be concluded that OHCT can improve ERPE in students.